Benchmarking Local Government Performance on Rural Sanitation : Learning from Himachal Pradesh, India - World Bank (Washington, DC, 2012)
Open defecation is a traditional behavior in rural India. Conventional rural sanitation programs have been based on the assumption that people defecate in the open because they are too poor to afford the cost of constructing a toilet. Therefore, subsidies for upfront capital costs were provided to generate demand for 'sanitation,' interpreted narrowly as a pour-flush toilet. These programs increased the reported coverage of household toilets but had a poor record with respect to toilet usage, cost-effectiveness, and sustainability. To address the shortcomings of conventional rural sanitation programs, the Government of India launched the Total Sanitation Campaign (TSC) in 1999, with the goal of achieving universal rural sanitation coverage by 2012. The Water and Sanitation Program's (WSP) Global Scaling up Sanitation Project (also known as Total Sanitation and Sanitation Marketing, or TSSM) leverages the TSC framework and resources. TSSM combines Community-Led Total Sanitation (CLTS) with sanitation marketing to help local governments effectively use their funds to end open defecation and achieve sustainable impact.